Relationship between sit-to-walk performance and visual perception in children with typical development: A preliminary study - Songvanich, Somnuek; Suriyaamarit, Duangporn; Boonyong, Sujitra (Journal of Associated Medical Sciences, 2024)
Background: Performance of sit-to-walk (STW) is developed along with improvement in neuromuscular control. Visual development plays an important role for motor learning and function in childhood. There was little evidence to indicate the relationship between visual function and motor performance. Objective: This study aims to examine the relationship between STW performance and visual perception in children with typical development. Materials and methods: Fifteen healthy children aged 7 to 12 years participated in the study. They were asked to complete the Development Test of Visual PerceptionThird Edition (DTVP-3). Motion capture was used to collect spatiotemporal data from five STW trials. The relationship between these spatiotemporal parameters and visual perceptual scores were analyzed by the Pearson correlation coefficient. Results: Positive moderate and high correlation were found between the eyehand coordination sub-score and the first (r=0.52, p<0.05) and second step width><0.05) and second step width (r=0.71, p<0.01) of STW, respectively. The second step width also correlated with the visual-motor integration composite (r=0.55, p<0.05). There was moderate correlation between the stride length and the copying subtest (r=0.52, p<0.05). ><0.05). Conclusion: This preliminary study demonstrated that some spatial parameters of STW performance were associated with the visual-motor abilities of the DTVP-3. This suggested that an improvement in motor performance is developed along with visual perceptual function especially motor involving task.